Dorsal column myelopathy after intrathecal chemotherapy for leukemia. Issue 2 (February 2017) - Pinnix, Chelsea C.; Chi, Linda; Jabbour, Elias J.; Milgrom, Sarah A.; Smith, Grace L.; Daver, Naval; Garg, Naveen; Cykowski, Matthew D.; Fuller, Greg; Cachia, David; Kamiya-Matsuoka, Carlos; Woodman, Karin; et al.
Abstract: Intrathecal chemotherapy with methotrexate, a folate antagonist, is widely used to treat central nervous system malignancies. The mechanisms underlying methotrexate‐induced neurotoxicity are unclear but may be related to increased homocysteine levels. Intrathecal methotrexate‐induced myelopathy mimicking subacute combined degeneration, with normal B12 levels, has been documented. We examined treatment and magnetic resonance imaging (MRI) characteristics of 13 patients with leukemia who received intrathecal methotrexate and developed urinary and bowel incontinence, ascending motor weakness, and sensory loss with dorsal column hyperintensity on MRI between 2000 and 2016. Cerebrospinal fluid evaluation was negative for leukemia in all patients and positive for elevated protein in 12 patients. Seven of eight patients with available data had reduced serum folate, increased serum homocysteine, or both, implicating methotrexate as the cause of neurotoxicity. Autopsy of one patient revealed loss of myelinated axons in the posterior columns. These findings suggest that methotrexate neurotoxicity may be mediated by folate antagonism. Awareness and a high index of suspicion of these characteristic clinical and radiographic features in patients who develop myelopathy after intrathecal methotrexate may help to avoid additional neurotoxic therapy in such patients.